Impact of mega sport events on hosting countries' stock market - Cheng, Fan Fah; Hwa, Tee Hai (WorldConferences.net, 2014)
This paper examines the impact of the international sporting events on hosting country stock market. A total of 30 international sporting events had been utilized in this study where it comprises of five major sporting events namely Summer Olympics Games, Winter Olympics Games, FIFA World Cup, European Football Championships and Commonwealth Games. In particular, this study uses event study methodology to analyse and investigate the stock reaction toward the event announcement date and event starting month. The empirical result indicate that there is short term positive effect on announcement date across whole stock market of event hosting country but the result indicates no long term positive effect after event starting month.